A aquisição da língua inglesa usando as novas tecnologias da informação e comunicação : a apropriação do conhecimento - Campos, Artur André Martinez (2008)
This work is aimed at studying the English language acquisition of the skills of Reading and Listening through the use of ICT. The Knowledge Society is characterized by information sharing and new approaches to learning that certainly will reward those students familiar with Information Technologies. The investigation to verify language learning autonomy was done through the interaction of students and ontologies created to English language learning. The research was performed using websites containing grammar exercises, reading comprehension activities as much as newspapers and magazines online from the U.S.A, U.K., and others aimed to the development of the reading skills; while websites containing podcasts and AM/FM radio station websites were used to develop listening skills. This language acquisition was verified through a qualitative research using the case study method. A participative investigation was conducted by a semi-structured interview which gathered data using the SILL quiz. This study researches a new approach to English language acquisition using the Internet due to the ubiquity of computers nowadays.